Tourism discourse and medical tourists' motivations to travel. Issue 2 (15th June 2015) - Adams, Krystyna; Snyder, Jeremy; Crooks, Valorie; Johnston, Rory
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to respond to a knowledge gap regarding the motivations of medical tourists, the term used to describe persons that travel across borders with the intention of accessing medical care. Commonly cited motivations for engaging in medical tourism are typically based on speculation and provide generalizations for what is a contextualized practice. This research paper aims to complicate the commonly discussed motivations of medical tourists to provide a richer understanding of these motivations and the various contexts in which medical tourists may choose to travel for medical care. Design/methodology/approach – Drawing on semi-structured interviews with 32 former Canadian medical tourists, this study uses the Iso-Ahola's motivation theory to analyze tourists' motivations. Quotations from participants were used to highlight core themes relevant to critical theories of tourism. Findings – Participants' discussions illuminated motivations to travel related to personal and interpersonal seeking as well as personal and interpersonal escaping. These motivations demonstrate the appropriateness of applying critical theories of tourism to the medical tourism industry. Research limitations/implications – This research is limited in its ability to link various motivations with particular contexts such as medical procedure and personal demographics. However, this study demonstrates that the three commonly cited motivations of medical tourists might oversimplify this phenomenon. Originality/value – By providing new insight into medical tourists' motivations, this paper expands the conversation about medical tourists' decision-making and how this is informed by tourism discourse. This insight may contribute to improved guidance for medical tourism stakeholders for more ethical and safe practices.